Comparative efficacy of tisagenlecleucel and lisocabtagene maraleucel among adults with relapsed/refractory large B-cell lymphomas: an indirect treatment comparison. Issue 4 (21st March 2022) - Schuster, Stephen J.; Zhang, Jie; Yang, Hongbo; Agarwal, Abhijit; Tang, Wenxi; Martinez-Prieto, Marcela; Bollu, Vamsi; Kuzan, David; Maziarz, Richard T.; Kersten, Marie José
Abstract: This study compared overall survival (OS), progression-free survival (PFS), complete response rate (CRR), and overall response rate (ORR) of tisagenlecleucel (tisa-cel) and lisocabtagene maraleucel (liso-cel) in relapsed or refractory large B-cell lymphomas (r/r LBCL). Using matching-adjusted indirect comparison (MAIC), individual patient-level data from JULIET (tisa-cel) were weighted to match the patient population in TRANSCEND (liso-cel). The main analysis compared infused JULIET patients ( N  = 106) with the TRANSCEND efficacy-evaluable set (EES) ( N  = 256 [infused]). After adjustment, OS, PFS, and the CRR were comparable between tisa-cel and liso-cel EES patients. The estimated adjusted 2-year OS, 2-year PFS, ORR, and CRR were 45.6, 38.2, 62.9, and 47.7%, respectively, for tisa-cel vs. 43.8, 42.1, 72.7, and 53.1% for liso-cel. A scenario analysis compared JULIET patients to the TRANSCEND primary analysis set (PAS) ( N  = 133). ORR was significantly higher in the TRANSCEND PAS compared with matched JULIET patients, but no significant differences in CRR were observed.